2017
DOI: 10.1111/liv.13478
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for non‐alcoholic fatty liver disease: A 7‐year follow‐up study among urban, adult Sri Lankans

Abstract: In this community cohort study, the annual incidence of NAFLD was 6.2%. Incident NAFLD was associated with general and central obesity, raised triglycerides and diabetes, and showed a tendency of association with PNPLA3 gene polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 22 publications
3
31
0
Order By: Relevance
“…In the current study, there was a high prevalence of NAFLD in urban population (n = 45, 64.29%) than rural ones (n = 25, 35.71%). This matches the study of Niriella et al, (2017) who reported that the urban cohort, when followed up for 7 years and subjected to ultrasonography of the liver again, showed their prevalence of NAFLD had increased dramatically to nearly 66% in that age (42 -71 years) population. The annual incidence of NAFLD in this population was 6.6% [13].…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, there was a high prevalence of NAFLD in urban population (n = 45, 64.29%) than rural ones (n = 25, 35.71%). This matches the study of Niriella et al, (2017) who reported that the urban cohort, when followed up for 7 years and subjected to ultrasonography of the liver again, showed their prevalence of NAFLD had increased dramatically to nearly 66% in that age (42 -71 years) population. The annual incidence of NAFLD in this population was 6.6% [13].…”
Section: Discussionsupporting
confidence: 90%
“…Fourthly, exploratory subgroup and interaction analyses were used to evaluate effect modification in the adjusted models. Participants were stratified according to age, sex, and abdominal obesity because those grouping variables have been reported to be associated with NAFLD risk [19][20][21][22]. Age was classified as < 60 and ≥ 60 years.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the age-standardized incidence of T2DM was 9.5 per 1000 person-years for men and 9.2 for women from 2006 to 2014 16 . A retrospective nationwide longitudinal study in Taiwan during 1999 to 2004 showed that age-standardized prevalence of T2DM increased from 4.7 to 6.5% for men and from 5.3 to 6.6% for women 17 .…”
Section: Discussonmentioning
confidence: 99%